La importancia relativa del análisis de los estados financieros en la toma de decisiones - Moran Sunción, Richard Geovanny (2015)
The company LECTORUNI S.A. throughout his career he has grown rapidly to the point that its accounting management has been increasing, which warrants greater control by the specific area, this is precisely what has created the problem in the financial statements, which is not enables appropriate decision making, this affects the proper business development, which is why this work has as main objective to design a manual that will allow proper analysis and interpretation of financial statements, so that the manager can turn make good and wise decisions always based on real and compelling figures. The methodology applied in this study is a qualitative research, descriptive, proactive and quantitative type, protocol and reclassification, collection, obtaining and comparing the accounting data in the financial statements of the company will continue, for it was a comprehensive review of financial reports to determine whether there is a relationship between the data they have and the incorporation of appropriate indicators. The main objectives are to present a comprehensive proposal to assess internally instrument ensuring the financial viability of the institution. The conclusions reached were not currently assesses the financial standards, the decisions you make based on the current financial statements management are inadequate since they have errors, current transfers that occur in cumulative results are not calculated at all values that manages the company, it is therefore recommended to evaluate the standards under which the financial activity of the company are grounded and correctly develop its financial statements because it directly influences the management decisions for success or failure economic management of the institution.